PENGGUNAAN METODE DALCROZE DALAM PEMBELAJARAN PIANIKA DI SMA NEGERI 1 TANJUNG RAJA - Syaflinawati, Syaflinawati (UNIVERSITAS INDO GLOBAL MANDIRI, 2021)
Pianica is a small wind instrument similar to a harmonica, using keyboard blades which has rangeabout three octaves, played by blowing using a flexible pipe connected to the mouth. Pianica learning is designed to train students mentally and physically so that they can interact with others in the form of interactions between students and teachers, the environment, and other learning resources. Furthermore, this study aims to explain the application of the dalcroze method in the pianica learning process and pianica playing techniques using the dalcroze method. The method used in this study refers to the qualitative method using data collection techniques obtained through observation, interviews and field documentation. The results of this study refer to: First, learning pianica is a practical lesson that is useful for improving the skills and abilities and skills of students in playing the musical instrument. In this context, learning dalcroze eurythmics is closely related to solphegio (hearing exercises), improvisation, and eurythmics. Second, the technique of playing the pianica using the dalcroze method is to provide insight and understanding of learning theory, as well as practice. In this case, learning pianica using the Dalcroze method helps the creativity of students in the learning process because it indirectly teaches students to be more thorough, understand and be sensitive to the circumstances or instincts they have.